KAJIAN JENIS POHON POTENSIAL UNTUK HUTAN KOTA DI BANDUNG, JAWA BARAT - Soleh Mulyana (Jurnal Analisis Kebijakan Kehutanan, 2013)
Economic growth and development in urban area tend to reduce green open space that has impact on the disruption of ecosystem balance, such as temperature increase, air and waterpollution, soil surface decrease and flood risk. Efforts to eliminate those negative impact can be conducted by the development of urban forest by using potential tree species. This study was aimed to investigate, how far the PP No.63/2002 on urban forest has been accommodated by local gaverment. Location for this study was the City of Bandung, that has issued local regulation (Perda) No.25/2009 on urban forest that identifies nine urban forests in Bandung namely. Taman Tegalega, Taman Pramuka, Taman Lantas, Taman Cilaki, Taman Maluku, TPA Pasir Impun, Kebun Binatang Tamansari, and PT Pindad urban Forest. Census method was applied in this study in order to identify urban forest coverage, tree structure,tree population,tree dimension (diameter,total height, branch-free height, canopy height and width) and tree identification (genus, species, and family). This study indicatedthatall urban forests, except PT Pindad urban Forest, were utilized as sport and recreation facilites. PT Pindad urban forest was restricted as it is located inside the army industry. The highest tree diversity was at the Kebun Binatang Tamansari while the lowest was at TPA Pasir Impun. Largest tree population was found at PT Pindad forest, while the lowest one was found at TPA Pasir Impun. Almost all of tree population composing urban forests in Bandung wereexotic species. Results of this study were used to program tree species suitability matrix based on tree description (characteristics and functions) of all suitable tree species for urban forest. This potential tree matrix is, there fore recommended be used by stakeholders as a reference to determine particular tree species for urban forest development. However, selection of tree species should consider the balance with endemic, rare and endanger species.